AKAD SALAM DALAM JUAL BELI ONLINE: PLATFORM TIKTOK SHOP - Khalda Khairunnisa; Resa Aulia; Mega Safitri; Ramanda Setiawan; Mukhlishotul Jannah (Cahaya Ilmu Bangsa, 2024)
This research examines the application of the salam contract in online transactions on the TikTok Shop platform, focusing on a case study of the store Gothfirt_id. A salam contract, as a form of transaction in Islamic law, allows payment to be made in advance for goods that will be received later. This study assesses the conformity of transaction practices on TikTok Shop with sharia principles and Islamic accounting standards regulated in PSAK 103, as well as the strengths and weaknesses of online buying and selling. Using a descriptive qualitative method, data were collected through observation, literature review, and interviews. The results indicate that Gothfirt_id has implemented the principles of salam by adopting advance payment policies, clear product descriptions, and adequate payment options, including Cash on Delivery (COD) and e-wallets. Additionally, the store complies with PSAK 103, covering aspects of recognition, measurement, and disclosure in financial reporting to enhance transparency and accountability. The study concludes that the application of salam in online sales on TikTok Shop can promote fair and sharia-compliant transactions while strengthening customer trust. These findings contribute to the literature on sharia-based e-commerce and the relevance of Islamic accounting standards in digital transactions.